Role of Rifaximin in Inflammatory Bowel Disease Treatment - Lia Scribano, Maria (Mini Reviews in Medicinal Chemistry, 2016)
Inflammatory bowel diseases are characterised by an altered composition of the intestinal microbiota, which may contribute to their development and maintenance in susceptible hosts. The involvement of bacteria in the inflammation has provided the rationale for a therapeutic manipulation of the gut flora through the use of antibiotics. However, the role of antibiotics has not been clearly demonstrated and their long-term employment is often restricted by an elevated number of adverse events. The use of rifaximin, which is characterised by an excellent safety profile thanks to its negligible intestinal absorption, appears to have some promise. Study results suggest that rifaximin could be useful in Crohn’s disease, and a new gastroresistant formulation (rifaximin-extended intestinal release) has recently shown its efficacy in patients with moderate Crohn’s disease. Less consistent data support the use of rifaximin in ulcerative colitis and in pouchitis, although the results of some studies have been encouraging. Further large controlled trials are warranted to confirm the role of rifaximin in inflammatory bowel disease treatment.
Keywords: pouchitis